How the internet become commercial: Innovation, privatization, and the birth of a new network - Greenstein, Shane (Princeton Princeton University Press, 2015)
In less than a decade, the Internet went from being a series of loosely connected networks used by universities and the military to the powerful commercial engine it is today. This book describes how many of the key innovations that made this possible came from entrepreneurs and iconoclasts who were outside the mainstream$1 (Band how the commercialization of the Internet was by no means a foregone conclusion at its outset.s